Indoor inhalation intake fractions of fine particulate matter: review of influencing factors. (14th December 2015) - Hodas, N.; Loh, M.; Shin, H.‐M.; Li, D.; Bennett, D.; McKone, T. E.; Jolliet, O.; Weschler, C. J.; Jantunen, M.; Lioy, P.; Fantke, P.
Abstract: Exposure to fine particulate matter (PM2.5 ) is a major contributor to the global human disease burden. The indoor environment is of particular importance when considering the health effects associated with PM2.5 exposures because people spend the majority of their time indoors and PM2.5 exposures per unit mass emitted indoors are two to three orders of magnitude larger than exposures to outdoor emissions. Variability in indoor PM2.5 intake fraction ( iF in, total ), which is defined as the integrated cumulative intake of PM2.5 per unit of emission, is driven by a combination of building‐specific, human‐specific, and pollutant‐specific factors. Due to a limited availability of data characterizing these factors, however, indoor emissions and intake of PM2.5 are not commonly considered when evaluating the environmental performance of product life cycles. With the aim of addressing this barrier, a literature review was conducted and data characterizing factors influencing iF in, total were compiled. In addition to providing data for the calculation of iF in, total in various indoor environments and for a range of geographic regions, this paper discusses remaining limitations to the incorporation of PM2.5 ‐derived health impacts into life cycle assessments and makes recommendations regarding future research.